Carbon metabolism and multidrug resistance in Bacillus mobilis and Cupriavidus campinensis isolated from cadmium-spiked soils - Akinwole, Philips O.; Jacobs, Emma E. C.; Shaffer, Nina G. (Frontiers in Environmental Science, 2025)
Heavy metal contamination and antibiotic resistance are critical environmental and public health challenges, often exacerbated by co-selection pressures in polluted environments. This study identifies and characterizes Bacillus mobilis and Cupriavidus campinensis, two cadmium-tolerant bacterial species isolated from cadmium-amended soils with cadmium (Cd2+) concentrations exceeding those typically found in highly contaminated soils. Both species exhibited multidrug resistance and the ability to metabolize specific carbon substrates, including pyruvic acid methyl ester, itaconic acid, D-galactonic acid-γ-lactone, Tween-40, and Tween-80. These substrates enhance microbial activity and heavy metal bioavailability, supporting their potential roles in bioremediation, especially through the targeted introduction of optimal carbon substrates. Antibiotic susceptibility testing revealed distinct growth dynamics under exposure to antibiotics such as ceftriaxone, ciprofloxacin, gentamicin, and tetracycline. Notably, C. campinensis displayed extended lag phases and concentration-dependent growth inhibition, with delayed recovery observed for ceftriaxone and doripenem. In contrast, B. mobilis exhibited resistance to several antibiotics, including erythromycin and vancomycin, and adaptive responses to ciprofloxacin, levofloxacin and nitrofurantoin, suggesting robust resistance mechanisms. These findings highlight the limitations of standard 24-h testing protocols, which fail to capture delayed adaptive responses critical for understanding resistance in complex environments. In silico resistome profiling of the isolates confirmed high-risk resistance genes, including β-lactamases (blaZ, mecA), fluoroquinolone targets (gyrA, parC), macrolide resistance genes (ermB, ermC), and tetracycline efflux pumps (tetK, tetL), consistent with environmental persistence and potential horizontal gene acquisition. Our study underscores the potential of B. mobilis and C. campinensis in bioremediation strategies for heavy metal-contaminated soils. Additionally, the co-selection of resistance to both Cd2+and antibiotics highlights the ecological complexity of contaminated environments. Future work should explore the molecular pathways driving these adaptive traits and extend susceptibility testing protocols to better assess bacterial responses under prolonged environmental and antibiotic stress.